The impact of new high-rise buildings on visual preference of historic districts: a case study of Shenyang, China - Xinlingyi Huang; Xuefeng Zhao (Journal of Asian Architecture and Building Engineering)
The new high-rise buildings have affected the overall spatial form of the original historic districts in the city, and how to balance the sense of incongruity between the two is a very critical issue. This study takes two representative new high-rise buildings in and around the Shenyang Road Historic District as the research object, selects seven key observation points as the shooting viewpoints, and chooses the relative height ratio, relative mass ratio and relative distance ratio of different viewpoints as the research variables. Then, the photo stimulation method of light stimulation experiment was conducted on the participants, and the rating results of the participants were used as the outcome variable. The results show that new high-rise buildings will have an impact on the external spatial form of the historic district. And the relative height, relative mass ratio, and relative distance ratio of new high-rise buildings are all influential factors in the public’s visual preference for historic districts. In addition, the range of these variables also has an effect on visual preference. The study proposes key parameters for new high-rise buildings and historic districts within a certain viewing area, providing a quantitative reference range for urban planning and urban renewal.